BRAND IMAGE DAN BRAND PERSONALITY SERTA PENGARUHNYA TERHADAP BRAND LOYALTY PADA PRODUK PIKOPI DI PURWAKARTA - Kusumadewi, Ade Nurhayati Kusumadewi Nurhayati; Risma Ismawanti, Nurul; Mawardi, Amna; Wahyudi, Robby (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This study aims to determine the influence of brand image and brand personality on brand loyalty in Pikopi products in Purwakarta. Using a quantitative approach, data were collected from 97 respondents through a non-probability sampling technique. The data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination (R²) with the help of IBM SPSS 25. The results show that both brand image and brand personality have a positive and significant partial effect on brand loyalty. Simultaneously, these independent variables also have a significant effect, with an F value of 70.961 and a significance level of 0.000. The R square value of 0.602 indicates that 60.2% of the variation in brand loyalty can be explained by brand image and brand personality. In conclusion, brand image and brand personality play a crucial role in building consumer loyalty toward Pikopi products in Purwakarta